Kolegium Recenzentów (2020) - Kosek, Jakub (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2021)
Dr hab. Małgorzata Bogunia-Borowska, prof. UJ, Uniwersytet Jagielloński, Polska Dr hab. Elżbieta Durys, Uniwersytet Warszawski, Polska Dr hab. Barbara Giza, prof. SWPS, SWPS Uniwersytet Humanistycznospołeczny, Polska Dr hab. Witold Jakubowski, prof. UWr, Uniwersytet Wrocławski, Polska Dr hab. Małgorzata Lisowska-Magdziarz, prof. UJ, Uniwersytet Jagielloński, Polska Dr hab. Agnieszka Nieracka, Uniwersytet Śląski w Katowicach, Polska Prof. dr hab. Dariusz Rott, Uniwersytet Śląski w Katowicach, Polska Prof. dr hab. Katarzyna Skowronek, Akademia Górniczo-Hutnicza w Krakowie, Polska Dr hab. Paweł Tański, prof. UMK, Uniwersytet Mikołaja Kopernika w Toruniu, Polska